The Practice and Challenges of Differentiated Instruction Implementation: A Case Study at SMP Islam de Green Camp - Muhammad Aiman Zaidan Kusasi; Hanifah; Rona Elfiza (Jurnal Pendidikan dan Kebudayaan, 2024)
This study explores the strategies employed by English teachers at SMP Islam De Green Camp, Tanjungpinang, for implementing Differentiated Instruction in alignment with the Kurikulum Merdeka in English classes, as well as the challenges they face in doing so. A descriptive qualitative approach was used, incorporating observations, interviews, questionnaires, and documentation. The participants included three English teachers, six inclusive students, and fifty-two regular students. Data were analyzed using the Miles and Huberman model, which involves data reduction, data display, and conclusion drawing. The findings reveal that the implementation of Differentiated Instruction at this school is still developing, with content differentiation requiring further enhancement compared to other aspects of differentiation. Teachers are actively adapting teaching strategies, assessments, and classroom environments to meet diverse student needs. Key challenges include varying learning needs, students’ negative attitudes towards English, and limited vocabulary and memorization skills. Despite these obstacles, teachers remain committed to advancing the practice of Differentiated Instruction through professional development, collaboration, and innovative teaching methods. In conclusion, while the implementation of Differentiated Instruction at SMP Islam De Green Camp is progressing, ongoing efforts in professional development and resource allocation are crucial to fully realizing its potential to support diverse student needs within the Kurikulum Merdeka framework.